Step * 3 of Lemma i-member-convex'


1. Interval
2. : ℝ
3. : ℝ
4. a ∈ I
5. b ∈ I
6. {z:ℝr0 < z} 
7. {z:ℝr0 ≤ z} 
8. {z:ℝr0 ≤ z} 
9. (x y) z
10. ((x/z) a) ((r1 (x/z)) b) ∈ I
⊢ ((x a) (y b)/z) ∈ I
BY
(Assert (((x/z) a) ((r1 (x/z)) b)) ((x a) (y b)/z) BY
         (nRMul ⌜z⌝ 0⋅ THEN Auto)) }

1
.....aux..... 
1. Interval
2. : ℝ
3. : ℝ
4. a ∈ I
5. b ∈ I
6. {z:ℝr0 < z} 
7. {z:ℝr0 ≤ z} 
8. {z:ℝr0 ≤ z} 
9. (x y) z
10. ((x/z) a) ((r1 (x/z)) b) ∈ I
⊢ ((a x) -(b x) (b z)) ((a x) (b y))

2
1. Interval
2. : ℝ
3. : ℝ
4. a ∈ I
5. b ∈ I
6. {z:ℝr0 < z} 
7. {z:ℝr0 ≤ z} 
8. {z:ℝr0 ≤ z} 
9. (x y) z
10. ((x/z) a) ((r1 (x/z)) b) ∈ I
11. (((x/z) a) ((r1 (x/z)) b)) ((x a) (y b)/z)
⊢ ((x a) (y b)/z) ∈ I


Latex:


Latex:

1.  I  :  Interval
2.  a  :  \mBbbR{}
3.  b  :  \mBbbR{}
4.  a  \mmember{}  I
5.  b  \mmember{}  I
6.  z  :  \{z:\mBbbR{}|  r0  <  z\} 
7.  x  :  \{z:\mBbbR{}|  r0  \mleq{}  z\} 
8.  y  :  \{z:\mBbbR{}|  r0  \mleq{}  z\} 
9.  (x  +  y)  =  z
10.  ((x/z)  *  a)  +  ((r1  -  (x/z))  *  b)  \mmember{}  I
\mvdash{}  ((x  *  a)  +  (y  *  b)/z)  \mmember{}  I


By


Latex:
(Assert  (((x/z)  *  a)  +  ((r1  -  (x/z))  *  b))  =  ((x  *  a)  +  (y  *  b)/z)  BY
              (nRMul  \mkleeneopen{}z\mkleeneclose{}  0\mcdot{}  THEN  Auto))




Home Index